Creating a culture of risk in the Greek public administration: A brief retrospect on the memorandum era - Iordanis Eleftheriadis; Vasilios Vyttas (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2016)
Purpose -The recent financial crises in America and Europe have shown emphatically that the findings of the relevant risk management literature concluding that lurking risks can be converted into opportunities have unfortunately not informed policy. The assumption of the risk as a burden, often leads economies to crises that undermine the development and prosperity of states and citizens. In this context, this article aims at highlighting risk characteristics and presentation of basic management principles which should govern the operation of public service organizations. The aim of the present paper is also to highlight the dual nature of risk. Risk is frequently uni-dimensionally perceived by people. Usually, its usefulness in effecting change and making the most of the manifold opportunities of the contemporary volatile environment is ignored. Design/methodology/approach -There has been an extensive literature review on risk culture (organizations and personnel). Elements of the Greek Economy were used as well. Findings -The significance of developing a risk culture in organizations and governments. However, the unsuccessful attempt which was made by the Greek state so as to deal with the risks, shows that minimal preparation and progress has been achieved. Based on literature review of the economic facts of the 2008-2015 period in Greece, the fact that emerges is that effective risk management is a necessary condition for the survival of public organizations in today's global environment. Research limitations/implications-In relation to risk-taking by employees as well as their financial and operational risks in Public Administration and Economics, is ascertained that there are few studies, as opposed to the interest in the importance of taking risks in the strategy, which has risen sharply in recent years. Originality/value _ The provision of the theoretical framework for the development of a risk management culture in organizations since the States are under restructuring scheme.
Keywords: H3; M10; 330; Risk; financial crises; culture of risk